Negotiating the right path: Working together to effect change in healthcare service provision to Aboriginal peoples - Wright, Michael; O'Connell, M. (2015)
This paper outlines the centrality of a Nyoongar worldview to an engagement framework designed with the Nyoongar community to enable the community to work meaningfully with service providers in the mental health and drug and alcohol sectors to bring about systems change. This paper follows on from a previous paper by the author (Wright 2011) in which the principles and methods of both Indigenous research and participatory action research are explored in relation to each other as a way of mitigating the delegitimising effects of colonisation. Privileging a Nyoongar worldview disrupts the dominant western paradigm so that service providers and the Nyoongar community can meaningfully work together to change the way services are provided to Nyoongar people experiencing mental health and drug and alcohol concerns, and indeed offer a way forward in working with other Aboriginal communities.